A Control Strategy for Two-stage PV Grid-connected Inverter Based on Voltage Oriented Control. Issue 1 (January 2020) - Zhang, Yiyan; Tang, Xiaobo; Shen, Zhongyu; Chen, Xiao; Feng, Yulong; Xu, Yanwei
Abstract: For the design of three-phase two-stage grid-connected PV inverter, the topology and control strategy of two-stage grid-connected inverter are analyzed. For the DC/DC converter control strategy, the shortcoming of conventional perturbation and observation method are analyzed, which is difficult to obtain high response speed and steady-state tracking accuracy due to its fixed disturbance step size. A duty cycle self-optimizing MPPT method is adopted and effectively alleviates the contradiction between tracking speed and accuracy. For the DC/AC converter control strategy, the grid voltage oriented vector control is adopted based on the analysis of the mathematical model of rotating coordinate. The current decoupling and grid voltage feedforward control in dq coordinate system are carried out. The control system parameters are designed and verified to be feasible.